TANGGAPAN VARIETAS JAGUNG HIBRIDA DAN KOMPOSIT PADA PEMBERIAN PUPUK TUNGGAL N, P, K DAN PUPUK KANDANG DI LAHAN KERING - M. P. Sirappa; Maryam Nurdin (Universitas Lampung, 2010)
Experiments conducted in the village Waihatu, Part West Ceram district in 2009. The aim of research was to determine the response of two varieties of maize hybrids and one maize composites on a single fertilizer N, P, K and chicken manure on dry land. The experiment is based on randomized block design with three replications. Experimental plots measuring 15 mx 16 m, spacing 75 cm x 40 cm, 2 plants /hole. Varieties was studied are Bima-3 Bantimurung and Bisi-2 (maize hybrid) and Srikandi Kuning-1 (maize composite). Dosage of fertilizer used is 300 kg urea, 200 kg of SP-36, 50 kg of KCl, and 2 tons of chicken manure/ha. The results showed that Bima-3 Bantimurung variety was give average growth and yields is higher than maize of Srikandi Kuning-1 and Bisi-2. The average yield of Bima-3 Bantimurung, Bisi 2, and Srikandi Kuning-1 on providing a single fertilizer N, P, K and chicken manure are 8.71 t/ha, 6.42 t/ha, and 4.50 t/ha, respectively. Varieties Bima-3 Bantimurung and Srikandi Kuning-1 have a pretty good prospect to be developed on dry land because bisade high productivity and tolerance to environmental stress (drought), also Bima-3 Bantimurung variety have high biomass and leaf remained green until the harvest, while Srikandi Kuning-1 is rich protein and essential amino acids. Key-words: response, single fertilizer N, P, K, chicken manure, dry land.